Cadherin Signaling in Cancer: Its Functions and Role as a Therapeutic Target - Yu, Weina; Yang, Li; Li, Ting; Zhang, Yi (Frontiers in Oncology, 2019)
Cadherin family includes lists of transmembrane glycoproteins which mediate calcium-dependent cell-cell adhesion. Cadherin-mediated adhesion regulates cell growth and differentiation throughout life. Through the establishment of the cadherin-catenin complex, cadherins provide normal cell-cell adhesion and maintain homeostatic tissue architecture. In the process of cell recognition and adhesion, cadherins act as vital participators. As results, the disruption of cadherin signaling has significant implications on tumor formation and progression. Altered cadherin expression plays a vital role in tumorigenesis, tumor progression, angiogenesis, and tumor immune response. Based on ongoing research into the role of cadherin signaling in malignant tumors, cadherins are now being considered as potential targets for cancer therapies. This review will demonstrate the mechanisms of cadherin involvement in tumor progression, and consider the clinical significance of cadherins as therapeutic targets.